2022
DOI: 10.2478/hukin-2022-0094
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Variable Resistance Training within Complex Training on Neuromuscular Adaptations in Collegiate Basketball Players

Abstract: The aim of this study was to investigate the differences in neuromuscular performance between variable resistance training and constant resistance training within complex training. Twenty-one well-trained collegiate basketball players were randomly assigned to either an experimental group (variable resistance training) or a control group (constant resistance training) and completed a twice weekly training program over an 8-week period. Training programs were the same except that the experimental group included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
4
0
3
Order By: Relevance
“…Despite the time management benefit we can also expect performance enhancement regarding a whole training block. 39 Apart from the PAPE protocols the addition of accommodating resistance was also found to be more effective than solely free weight resistance training to develop lower body power 40 or maximal strength. 41 Additionally, several systematic reviews and meta-analyses 42 , 43 , 44 proved that the accommodating resistance may be superior or equally effective in improving maximal muscle strength and power.…”
Section: Discussionmentioning
confidence: 98%
“…Despite the time management benefit we can also expect performance enhancement regarding a whole training block. 39 Apart from the PAPE protocols the addition of accommodating resistance was also found to be more effective than solely free weight resistance training to develop lower body power 40 or maximal strength. 41 Additionally, several systematic reviews and meta-analyses 42 , 43 , 44 proved that the accommodating resistance may be superior or equally effective in improving maximal muscle strength and power.…”
Section: Discussionmentioning
confidence: 98%
“…This may explain why we did not observe a difference in explosive power between the two groups after the 5-week training. Shi et al 35 found that after an intervention twice a week for 8 weeks, DST showed signi cant improvement in the squat jump (P = 0.014) compared with consistent resistance training.…”
Section: Discussionmentioning
confidence: 99%
“…O intitulado treinamento complexo incorpora pares de exercícios com semelhança de ordem cinesiológica. Ou seja, conjuga-se um exercício de força máxima com um exercício de força explosiva (Shi et al, 2022;Freitas et al, 2017;Freitas et al, 2019). Dois estudos mostraram que os protocolos com o treinamento complexo seriam uma metodologia versátil para estimular a força máxima.…”
Section: )unclassified